Acute myocardial infarction with ST-segment elevation in young patient with Bardet – Biedl syndrome - I.M. Sichkaruk; O.V. Khrystyuk; M.Ye. Romaniv; O.A. Vasylkova; O.S. Kargol; M.M. Pavelko; A.V. Yagensky (Кардіохірургія та інтервенційна кардіологія)
Acute myocardial infarction (MI) with ST segment elevation (STEMI) remains one of the most common causes of death in patients with coronary artery disease. The number of STEMIs among men aged 25–50 years has been rising in recent years. According to a number of studies, mortality from MI among young men in Ukraine is 3–5 times higher than in economically developed countries. Described case of STEMI in a young man with a genetic defect, which is part of a metabolic abnormality, may be the result of the atherosclerotic process progression. This case of Bardet – Biedl syndrome and MI with angiographically damaged coronary arteries in a man of 22 years demonstrates underestimation of the role of genetic diseases in the development of coronary artery disease in young patients. Active treatment of all risk factors along with monitoring of laboratory parameters in adolescents and young men with metabolic disorders, especially obesity and genetic diseases accompanied by metabolic disorders, is a prerequisite for prevention of coronary artery disease and, in particular, MI at young age.